2014
DOI: 10.1038/ncomms6408
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genetics affects miR-122 requirements and response to miR-122 inhibitors

Abstract: Hepatitis C virus (HCV) replication is dependent on a liver-specific microRNA (miRNA), miR-122. A recent clinical trial reported that transient inhibition of miR-122 reduced viral titers in HCV infected patients. Here we set out to better understand how miR-122 inhibition influences HCV replication over time. Unexpectedly, we observed the emergence of a HCV variant that is resistant to miR-122 knockdown. Next-generation sequencing revealed that this was due to a single nucleotide change at position 28 (G28A) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
3
72
0
Order By: Relevance
“…For example, miR-122 has two seed-binding sites in the 5=UTR of the HCV RNA genome that are upstream of the internal ribosomal entry site and are necessary for viral replication (34). Reduced miR-122 binding decreases, while increased binding elevates HCV replication (3,22). Alternatively, we have postulated a role for apoptosis in HCV propagation, and miR-34a is known to regulate apoptosis in hepatocytes (10).…”
mentioning
confidence: 99%
“…For example, miR-122 has two seed-binding sites in the 5=UTR of the HCV RNA genome that are upstream of the internal ribosomal entry site and are necessary for viral replication (34). Reduced miR-122 binding decreases, while increased binding elevates HCV replication (3,22). Alternatively, we have postulated a role for apoptosis in HCV propagation, and miR-34a is known to regulate apoptosis in hepatocytes (10).…”
mentioning
confidence: 99%
“…2b, c), suggesting that these viruses are still dependent on miR-122. A recent study showed that HCV recombinant Jc1 with a G1A change in the S1 site (G28A in the genotype 2a genome) was selected from miR-122-antagonized Huh7.5 cells and was responsible for virus resistance to miR-122 inhibition (Israelow et al, 2014). We here tested G fi A, G fi U and G fi C changes at position 1 of the S1 and found that these mutations did not appear to affect the replication of the virus, with a high percentage of infected cells on day 1 post-transfection (Table 2 and Li et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated previously that introduction of selected mutations in the miR-122 binding site S1 conferred virus resistance to miravirsen treatment in cell culture (Li et al, 2011a); subsequent studies identified virus resistant to miravirsen treatment (Israelow et al, 2014;Ottosen et al, 2015). These observations indicate that HCV therapy using miR-122 antagomirs would also encounter the issue of virus escape.…”
Section: Introductionmentioning
confidence: 89%
“…We expressed ApoE or CAMP in 293T cells expressing CLDN1 (Fig. 8D) and infected them with an HCV mutant possessing a G28A substitution in the 5= untranslated region (UTR) of the genotype 2a JFH-1 strain (HCV122KO) that facilitates viral RNA replication in miR-122-deficient Huh7.5.1 cells (60). The results showed that the expression of CAMP has no effect on the replication of HCV122KO (Fig.…”
Section: Expression Screening and Identification Of Campmentioning
confidence: 99%